XML : a manager's guide - Dick, Kevin, 1969- (Addison-Wesley, 1999)
"This book serves as a concise guide for technical managers, as well as a starting point for developers interested in taking advantage of XML. It uses clear explanations of XML essentials as a foundation to demonstrate how this technology can substantially benefit your organization. Designed to let you access exactly the information you require, this book clearly delineates different paths through the chapters based on your needs, provides executive briefings for every chapter, and includes fast-track summaries of major points in the margins."--BOOK JACKET.